Zintegrowany System Informacji Archiwalnej (ZoSIA) w archiwach państwowych. Informacje wstępne - Staszewska, Hanna (Przegląd Archiwalny Instytutu Pamięci Narodowej, 2023)
The article includes the basic data regarding the Integrated Archive Information System (ZoSIA) that has been implemented since 2007 in the state archives (up to March 2015 it functioned in seven archives). It replaces the current SEZAM (Evidence System of Archival Resources) and IZA (Inventories of Archival Fonds) bases combining their functions and allowing for registration of the archival resource (keeping accession and de-accession registers, registers of dislocation of the fonds and team inventory) as well as the inventory and preparation of the archival, photographic, technical, volatile documentation and cartography, recordings and films. ZoSIA also possesses the extended reporting module (particularly useful for reporting purposes) as well as the search engine. The system acts as the application in the Internet, thus it does not require financial resources for additional equipment or software. The data introduced into the system is automatically gathered and stored in the repository of the National Digital Archive in Warsaw.